A Randomized Controlled Trial of Listening to Recorded Music for Heart Failure Patients: Study Protocol. Issue 2 (March 2016) - Burrai, Francesco; Hasan, Wohaib; Fancourt, Daisy; Luppi, Marco; Di Somma, Salvatore
Abstract : Aims: To describe a conceptual framework and to test the effectiveness of a recorded music-listening protocol on symptom burden and quality of life in heart failure (HF) patients. Background: Heart failure is an important public health problem. Many HF patients experience symptoms burden and poor quality of life, even with current improvements in pharmacological treatments. Recorded music listening has been shown to improve outcomes in cardiovascular patients, but it has never been tested on HF patients and with a specific music protocol and a randomized controlled trial methodology. Methods: This study is a multicenter blinded randomized controlled trial that will involve 150 patients. Eligible patients will have a diagnosis of HF, in New York Heart Association functional classification of I to III, and will be recruited from 3 large hospitals in Northern Italy. Patients will be randomly allocated in a 1:1 ratio to receive recorded music-listening intervention with or without standard care for 3 months. Data will be collected at baseline and at the end of the first, second, and third month during the intervention, and at 6 months for follow-up. The following variables will be collected from HF patients with validated protocols: quality of life (primary endpoint), use of emergency services, rehospitalization rates, all cause mortality, self-care, somatic symptoms, quality of sleep, anxiety and depression symptoms, and cognitive function. Discussion: This study will examine the effect of recorded music listening on HF patients and will inform clinical practice. If the findings are found to be positive, the protocol could be used as a tool for evidence-based applications of recorded music in HF patients. The framework developed in this study may be helpful for future research focused on the effects of music in HF patients.